The Effectiveness of the Research and Development System in the Czech Republic and Taiwan in Relation to Economic Growth - Svobodová, Eliška; Kureková, Lucie; Krejčová, Nikola, 1974-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
This thesis examines the effectiveness of research and development (R&D) systems in the Czech Republic and Taiwan in relation to economic growth. The study applies endogenous growth theory to compare the institutional frameworks, funding mechanisms, and R&D performance indicators of the selected countries. Using annual data for the period 2000–2023 from international and national statistical sources, the thesis employs Fully Modified Ordinary Least Squares (FM-OLS) and Ordinary Least Squares (OLS) models to estimate the long- and short-run relationships between R&D indicators and GDP per capita. The results show that in the Czech Republic, human capital in the form of researchers has the strongest positive impact on economic growth, while in Taiwan, R&D expenditure and patenting activity have a significant positive long-run effect. In both countries, the short-run effects are limited. The added value of this thesis derives from its comparative analysis of two distinct economic and innovation systems, which have rarely been directly examined side by side in existing literature.
Vedoucí práce: Lucie Kureková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses